A review of how teachers are using the renewable energy materials in their lessons - Lambrechts, Therese (Rhodes University, Faculty of Education, Department of Education, 2017)
Climate change and renewable energy have recently become part of the school curriculum in South Africa. Many teachers at the secondary school level thus have to teach topics with which they are not (necessarily) familiar. The Centre for Renewable and Sustainable Energy Studies at Stellenbosch University has established a schools' programme to provide materials to aid the educators in the teaching of renewable energy topics. A research-based set of Learning Teaching Support Material (LTSM) was developed for high school educators. The learning material includes a DVD, PowerPoint presentations, posters, a teacher's manual, and assignments that can be used in different subjects. This study reports and reviews how teachers are currently using the material. Teacher accounts of materials use and evidence of learning in students work were solicited using an appreciative inquiry review process. The data reflected the value being created through patterns of materials use. A Vygotskian based task sequencing framework of Anne Edwards was used to examine the patterns of use which support learning. The use of the task sequencing as an analytical lens allowed the review to probe how knowledge representation was the primary use by teachers. Here they introduced learners to key concepts and to broaden their knowledge on renewable energy. The activities served to scaffold a clear learning progression but the activities were not strongly enough orientated towards ESD as learner-led processes of enquiry and action. The outcomes of the study will be used to update and better align the materials with a need for teachers to strengthen important ESD outcomes in the current curriculum.
Keywords: Renewable energy sources -- Study and teaching -- South Africa; Renewable energy sources -- Study and teaching -- South Africa -- South Africa; Curriculum evaluation -- South Africa; Environmental education -- South Africa